2013
DOI: 10.1039/c3cc00249g
|View full text |Cite
|
Sign up to set email alerts
|

A PdAg bimetallic nanocatalyst for selective reductive amination of nitroarenes

Abstract: Herein we have identified an optimal catalyst, Pd1Ag1.7, for the tandem reductive amination between nitroarenes and aldehydes (selectivity > 93%). Key to the success is the ability to control the compositions of the investigational Pd1-xAgx (x = 0-1) catalysts, as well as the clear composition dependent activity/selectivity trend observed in this study. This catalyst features a wide substrate scope, excellent recyclability, activity and selectivity under ambient conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…The conditions applied herein for the amination or amidation reaction of aryl halides lead to a convenient procedure and better yields in overall shorter reaction times than in previous studies with other heterogeneous or homogeneous catalyst systems. [37][38][39][40][41][42][43][44] Therefore, because of its mild reaction conditions and its compliance with green chemistry principles, our methodology has the potential to be used in the CÀN bond formation whether in a laboratory or an industrial process. In addition, complete removal of the metalbased catalyst from the reaction media makes it possible to use this method in pharmaceutical and other sensitive synthetic procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conditions applied herein for the amination or amidation reaction of aryl halides lead to a convenient procedure and better yields in overall shorter reaction times than in previous studies with other heterogeneous or homogeneous catalyst systems. [37][38][39][40][41][42][43][44] Therefore, because of its mild reaction conditions and its compliance with green chemistry principles, our methodology has the potential to be used in the CÀN bond formation whether in a laboratory or an industrial process. In addition, complete removal of the metalbased catalyst from the reaction media makes it possible to use this method in pharmaceutical and other sensitive synthetic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…[ [37][38][39][40] In 2013, Kumar et al reported a copper ferrite catalyst system for the same reaction. [41] These copper ferrite nanoparticles were previously used by Sun et al in the CÀO bond formation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the use of amine-borane complex as reductant is very effective for the preparation of monodispersable NPs. For example, Li and coworkers [29] reported that uniform PdAg NPs could be synthesized by borane-tert-butylamine complex. Sun et al [30] reported that monodisperse Pd NPs could be synthesized by tributylamine-borane complex.…”
Section: Synthesis and Characterization Of Aupd Alloy Npsmentioning
confidence: 98%
“…Recently, bimetallic nanomaterials (e.g., NPs) have emerged as a promising class of catalysts for a variety of chemical reactions . In many cases, bi‐MNPs may show higher catalytic efficiency compared to their monometallic counterparts, most likely because of the strong synergistic effects of two integrated metals in one particle .…”
Section: Applications Of Bi‐mncsmentioning
confidence: 99%